2007
DOI: 10.1257/000282807780323460
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change in a Multisector Model of Growth

Abstract: We study a multi-sector model of growth with differences in TFP growth rates across sectors and derive sufficient conditions for the coexistence of structural change, characterized by sectoral labor reallocation, and constant aggregate growth path. The conditions are weak restrictions on the utility and production functions commonly applied by macroeconomists. We present evidence from US twodigit industries that is consistent with our predictions about structural change and successfully calibrate the historica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
327
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(343 citation statements)
references
References 3 publications
13
327
2
1
Order By: Relevance
“…change shown, e.g., by Baumol (1967); theoretical relevance for structural change shown by, e.g., Ngai and Pissarides (2007).…”
Section: Differences In Tfp-growth Across Sectors -Empirical Relevancmentioning
confidence: 96%
See 4 more Smart Citations
“…change shown, e.g., by Baumol (1967); theoretical relevance for structural change shown by, e.g., Ngai and Pissarides (2007).…”
Section: Differences In Tfp-growth Across Sectors -Empirical Relevancmentioning
confidence: 96%
“…(Of course, the existence of neutral structural change requires some knifeedge conditions, which will be analyzed below, in our model.) Previously, Ngai and Pissarides (2007) have shown that neutral structural change can arise when all sectors have the same capital-intensity. However, Acemoglu and Guerrieri (2008) have shown that their results do not hold if capital-intensities differ across sectors, i.e.…”
Section: Then We Approach As Followsmentioning
confidence: 99%
See 3 more Smart Citations